Pharmacokinetic interactions between ivacaftor and cytochrome P450 3A4 inhibitors in people with cystic fibrosis and healthy controls - van der Meer, Renske; Wilms, Erik B; Sturm, Richart; Heijerman, Harry G.M. (Journal of cystic fibrosis, 2021)
•Current dosing recommendations when combining ivacaftor with CYP3A4 inhibitors can be maintained.•Exposure to ivacaftor was higher in healthy volunteers than in subjects with cystic fibrosis.•Pharmacokinetic parameters for ivacaftor in CF suggest decreased absorption, reduced half life time and larger volume of distribution compared to healthy individuals. Background: Ivacaftor is currently the only CFTR potentiator approved and is increasingly used since the development of CFTR correctors. Ivacaftor is metabolized by CYP3A4 and therefore dose reduction is required when treating patients on ivacaftor with CYP3A4 inhibiting drugs. As this advice is based on studies in healthy volunteers and not in cystic fibrosis (CF) patients, we need to investigate this in both groups to be able to extrapolate these data to CF. Methods: A cohort of CF patients and healthy subjects were exposed to a single dose of ivacaftor in combination with a strong (ritonavir), moderate (clarithromycin) and mild (azithromycin) CYP3A4 inhibitor. Ivacaftor concentrations were measured in all blood samples in order to calculate the pharmacokinetic parameters for ivacaftor. Results: We found that exposure to ivacaftor was higher in healthy volunteers than in subjects with CF. However this difference was not statistically significant. No differences were observed in the interaction potential of CYP3A4 inhibitors between both study groups. The strong CYP3A4 inhibitor ritonavir, increased exposure to ivacaftor 7 times. Conclusion: Our data support current recommendations for dose adjustment of ivacaftor in case of co-treatment with CYP3A4 inhibitors in people with CF. However, exposure to ivacaftor was higher in healthy subjects than in CF patients. Further study is needed to investigate the cause and implication of this difference.